Ubiquitous conceptual design of a ubiquitous application: A textile SME case study for real time manufacturing monitoring. (February 2015) - Mejía-Gutiérrez, Ricardo; Osorio-Gómez, Gilberto; Ríos-Zapata, David; Zuluaga-Holguín, Daniel
Abstract: Advances in Information and Communication Technologies (ICT), computing, networking, mechanics and electronics are changing the people's way of life. Several research efforts are leading the design and development of Artifact and Service Combination (ASC) with the implementation of Ubiquitous Technologies (UTs) in multidisciplinary sectors. However, the design process of such systems often ends in the implementation of conventional approaches and tools. A Ubiquitous Design Support Environment (UDSE) comprising an application intended to guide the different activities, tools and resources applied at the conceptual design stage is presented. After needs analysis, multidisciplinary collaborations are also required in order to generate innovative conceptual solutions, focusing this approach in the conceptual design stage of traditional design methods. Some activities from the conceptual design stage are enhanced through the use of the UDSE as well as through the use of a novel ubiquity assessment tool for concept selection and validation of Ubiquitous Products and Services. Finally, a case study on a Small and Medium Enterprise (SME) from textile sector, in a developing country, is presented to analyze and validate the presented concepts. Highlights: An index to evaluate the ubiquitous level of product-service systems was proposed. A framework integrating methods and tools supported the conceptual design stage. Hardware–Software were integrated through a Ubiquitous Design Support Environment. An industrial implementation allowed the evaluation of a Ubiquitous service.